2020
DOI: 10.3390/molecules25020350
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Magnetic Chitosan-Lipase B from Candida Antarctica Bioconjugates in the Enzymatic Kinetic Resolution of Racemic Heteroarylethanols

Abstract: Lipase B from Candida antarctica immobilized by covalent binding on sebacoyl-activated chitosan-coated magnetic nanoparticles proved to be an efficient biocatalyst (49.2–50% conversion in 3–16 h and >96% enantiomeric excess) for the enzymatic kinetic resolution of some racemic heteroarylethanols through transesterification with vinyl acetate. Under optimal conditions (vinyl acetate, n-hexane, 45 °C), the biocatalyst remains active after 10 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Another separation approach is the use of chiral (enantiopure) mobile phase additives for the formation of transient diastereomeric species in HPLC -besides other indirect approaches, such as derivatization with chiral species and subsequent separation of the resulting diastereomers (Peng et al 2016;Yu et al 2019;Ao et al 2022;Chen et al 2022;Bao et al 2022). Chiral/asymmetric synthesis (Xue et al 2018;Wojaczyńska and Wojaczyński 2020;Qian et al 2021;Zhu et al 2021;Sun et al 2022) and the kinetic resolution of enantiomers (Musa 2020;Spelmezan et al 2020;Harwood et al 2021; Huang racemic compounds or enantiomeric mixtures (Ikai and Okamoto 2009;Shen and Okamoto 2016;Yin et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Another separation approach is the use of chiral (enantiopure) mobile phase additives for the formation of transient diastereomeric species in HPLC -besides other indirect approaches, such as derivatization with chiral species and subsequent separation of the resulting diastereomers (Peng et al 2016;Yu et al 2019;Ao et al 2022;Chen et al 2022;Bao et al 2022). Chiral/asymmetric synthesis (Xue et al 2018;Wojaczyńska and Wojaczyński 2020;Qian et al 2021;Zhu et al 2021;Sun et al 2022) and the kinetic resolution of enantiomers (Musa 2020;Spelmezan et al 2020;Harwood et al 2021; Huang racemic compounds or enantiomeric mixtures (Ikai and Okamoto 2009;Shen and Okamoto 2016;Yin et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they showed a reasonable recyclability allowing ve up to ten cycles of recovery and reuse. [30][31][32][33] Interestingly, CAL-A presented much higher enzymatic activity in the trans-esterication of waste cooking oil 34 than PcL (Pseudomonas cepacian) and TLIM (Thermomyces lanuginosus) in a comparative study, demonstrating to be a suitable biocatalyst for that process leading to the formation of higher amounts of product at a lower activation energy. Those ndings provided a better understanding of the biocatalytic activity and showed that CAL-A can be promising for real applications.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent attachment of Lipase B from C. antarctica onto sebacoyl-modified chitosan-decorated MNPs constitutes a robust nanobiocatalyst to catalyze enzyme-assisted kinetic resolution of various racemic heteroarylethanols. It showed activity up to 10 repeated catalytic cycles under the optimized conditions (n-hexane, vinyl acetate, 45 °C) [61] . Manganese peroxidase isolated from Anthracophyllum discolor was immobilized to chitosan/magnetic Fe 3 O 4 biocomposite to eliminate reactive orange 16 and methylene blue dye pollutants.…”
Section: Polymer-modified Mnps For Enzyme Immobilizationmentioning
confidence: 99%
“… Saccharification of microcrystalline cellulose [60] Sebacoyl-modified MNPs Lipase B from Candida antarctica Chitosan High activity up to 10 repeated catalytic cycles under the optimized conditions (n-hexane, vinyl acetate, 45 °C). Enzymatic Kinetic Resolution of Racemic Heteroarylethanols [61] MNPs β -glucosidase from Thermotoga maritima Chitin, chitosan, and sodium alginate Marked reusability of the nanobiocatalytic system in several successive batches for GOS synthesis without a substantial loss of enzyme activity. Immobilized enzyme showed operational stability under varying pH, temperature, storage, and thermal conditions.…”
Section: Mof-modified Mnps For Enzyme Immobilizationmentioning
confidence: 99%